Integrating LP-WAN Communications within the Vehicular Ecosystem - Ramon Sanchez-Iborra; Jesús Sánchez-Gómez; José Santa; Pedro J. Fernández; Antonio F. Skarmeta (Journal of Internet Services and Information Security, 2019)
Vehicular communications are attracting the attention of both the academy and industry since some time ago. Most of the developed services rely on short-range communication technologies or on non-vehicular oriented cellular solutions such as 4G. In turn, during the last times a long-range transmission technology known as Low Power – Wide Area Network (LP-WAN) has gained great momentum. LP-WAN solutions such as LoRa (Long Range) promise long coverage ranges of about 10 km with very low power consumption. Since these features can improve the performance of many vehicular services, in this work the application of LoRa to the case of vehicular communications is explored. The two typical vehicular network architectures, namely, Vehicle-to-Infrastructure and Vehicle-to-Vehicle, are considered. The results, extracted from an experimental test-bench, show long coverage ranges never seen previously in vehicular environments. This opens the opportunity for developing novel services and applications in this growing ecosystem.